PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TTW (THINK TALK WRITE) UNTUK MENINGKATKAN KEMAMPUAN KOMUNIKASI MATEMATIKA DAN KEAKTIFAN SISWA (PENELITIAN DILAKSANAKAN DI KELAS VIII F SMP NEGERI 17 SURAKARTA TAHUN PELAJARAN 2016/2017) - Nugroho, Arif Agung; Sutopo, Sutopo; Pramesti, Getut (F.KIP Universitas Sebelas Maret, 2018)
This research aims to 1) describe the application of cooperative learning type TTW (Think Talk Write) to improve students? mathematics communication ability and activity of class VIII F SMP Negeri 17 Surakarta in academic year 2016/2017; 2) know the improvement of mathematics communication ability after following the learning of mathematics with cooperative learning type TTW; 3) know the improvement of students activity after following the learning of mathematics with cooperative learning type TTW. This research was a classroom action research conducted in 2 action cycles, with each cycle consisted of 3 meetings. The subjects of the research were 26 students of class VIII F SMP Negeri 17 Surakarta. The data which was collected in this research was learning implementation data, the results of mathematical communication skills test and data of students? activity. This research used observation to collect data of learning implementation and students? activity, then it used test to collect mathematical communication skills data. The indicators of success of this research are 1) the number of students who reach at least 50 % on minimum 2 criteria in each indicator of mathematical communication ability, 2) the number of students who have high activity category at least 60%. The result of the research concludes 1) the learning steps with cooperative learning type TTW could improve students? mathematical communication skills and activity consisted of: a) Introduction activity; b) Core activity, which is (1) the teacher delivers the material to be learned; (2) Stage 1: Think, students read and think about solving problems independently; (3) Stage 2: Talk (Speak), students work in groups, the formation of heterogeneous groups considered by the psychological aspects of students; (4) Stage 3: Write, the students rewrite the results of their discussion independently; (5) Stage 4: Presentation, c) Conclusion. 2) The percentage of mathematical communication ability in pre-action test is 3.85%, in the final test of the first cycle the percentage increased to 15.4% and in the final test of second cycle the percentage increased again to 57.7%. 3) The percentage of high category students activity on pre-action was 8.3%, in the first cycle percentage increased to 55.8% and in cycle II the percentage increased again to 86.2%. Based on the result of research, it can be concluded that the application of cooperative learning model of TTW type can improve students? mathematics communication ability and activity of class VIII F SMP Negeri 17 Surakarta in academic year 2016/2017